Factors influencing the behavior of the customers towards the servicescape offered by the Hang Jebat Stadium / Mohammad Fadly Mohamed Mansor - Mohamed Mansor, Mohammad Fadly (Faculty of Business and Management, 2007)
Malacca Stadium Corporation was established with the main objectives of marketing the Sport Event and offers other services for local and international. Its main function is to provide goods and quality services to enhance their customers' satisfaction with their company’s motto which is "Your Satisfaction is Our Priority". The main objective of this research is to study on "Factors that Influence Customers' Awareness towards Services offered by Malacca Stadium Corporation". Further, it is to know whether customers' are aware or not with the services offered by Malacca Stadium Corporation. For the purpose of this research, the descriptive and causal research was used, 58 questionnaires were distributed to customers of Malacca Stadium Corporation services, but only 48 questionnaires were managed to be collected using Nonprobability Sampling Technique. Questionnaires were distributed as the survey instrument as the source of primary data, other reliable resources would serve as secondary data.